THE INTERRELATION OF A. NEILL’ HERITAGE WITH PHILOSOPHICAL-PEDAGOGICAL THEORIES - Nekrutenko, Elena B.; Orlova, Yuliya V. (Educological discourse, 2015)
The interrelation of A. Neill’s heritage with philosophical-pedagogical theories was examined in the article. The free education ideas of reformatory Pedagogics (late XIX – early XX cent.) are the general pedagogical context of the formation of his pedagogical conception. We came to the conclusion that A. Neill’s pedagogical heritage is based on the philosophical understanding of the idea of freedom as the man’s natural state and it is closely interrelated with the worldview of famous philosophers and educators of different historical epochs (philosophy of early Daoism, existentialism), conceptions of free education theorists and practitioners (J.-J. Rousseau, M. Моntessori, L. Тоlstoy, C. Ventsel, E. Key, Н. Lane).